2017
DOI: 10.1186/s11689-017-9212-y
|View full text |Cite
|
Sign up to set email alerts
|

Attention and motor deficits index non-specific background liabilities that predict autism recurrence in siblings

Abstract: BackgroundRecent research has demonstrated that subclinical autistic traits of parents amplify the effects of deleterious mutations in the causation of autism spectrum disorder (ASD) in their offspring. Here, we examined the extent to which two neurodevelopmental traits that are non-specific to ASD—inattention/hyperactivity and motor coordination—might contribute to ASD recurrence in siblings of ASD probands.MethodsData from a quantitative trait study of 114 ASD probands and their brothers, 26% of whom also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
5
30
0
Order By: Relevance
“…Examples include Happé's Fractionable Autism Triad [Happe & Ronald, ] focused on the classical triad of social impairments, communicative impairments, and repetitive/restrictive behaviors and interest. Constantino's and colleagues' work demonstrates how the overlap of inherited core autism impairments, attentional impairments, and motor impairments lead to the full expression of ASD [Mous et al, ]. Both of these efforts rest on a parsing of only the cognitive aspects of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples include Happé's Fractionable Autism Triad [Happe & Ronald, ] focused on the classical triad of social impairments, communicative impairments, and repetitive/restrictive behaviors and interest. Constantino's and colleagues' work demonstrates how the overlap of inherited core autism impairments, attentional impairments, and motor impairments lead to the full expression of ASD [Mous et al, ]. Both of these efforts rest on a parsing of only the cognitive aspects of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond larger studies, studies that measure performance directly, and studies that sample in unbiased fashion, including from children both with and without ASD, longitudinal studies [Karmiloff‐Smith, ; Mous et al, ] and interventional studies may assist in more closely approximating causal relationships among genetic and brain‐based factors responsible for epilepsy, for regression and for the cognitive manifestations of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent contemporaneous analysis of symptom burden of non-ASD-specific neurodevelopmental traits and ASD recurrence in the siblings of affected probands ( Mous, Jiang, Agrawal, & Constantino, 2017 ) it was observed that Attention Deficit Hyperactivity Disorder (ADHD) symptoms and motor coordination impairment jointly accounted for a large share of the variance (over 50%) in both categorical ASD recurrence and quantitative trait severity of recurrent autistic syndromes in families affected by autism. These findings in a clinical family cohort confirmed observations from general population studies ( Lichtenstein, Carlstrom, Rastam, Gillberg, & Anckarsater, 2010 ), indicating substantial genetic overlap between the characterizing symptoms of autism and those of both inattention/hyperactivity and developmental coordination disorder.…”
Section: Introductionmentioning
confidence: 99%